Determinants of Strategic Information Management (Sim): A Case Study in a Malaysia Bank - Hussin, Norhayati Binti; Othman, Ahmad Soufiean; Jamaludin, Adnan (Qualitative and Quantitative Methods in Libraries, 2017)
Whether the banks in Malaysia really know what they are doing or just merely catching up with the global trends in banking business, the utilization of the information technology to realize their banking strategies is a phenomenon known as Strategic Information Management (SIM) to the researchers in the field of information management. SIM as reported in literatures could only happen within the framework of the existence of its determinants. Realizing it or not, banks that have successfully implement SIM would have placed these determinants surrounding their day to day running of their business. This case study, conducted in one of the most prominent bank in Malaysia that have successfully attained SIM showed that among the determinants that have existed in the bank are the government support, industry pressure, demand from competitive markets, information technology and business strategy, and information infrastructure. Apart from that, determinants such as top management support and IT personnel are the determinants that buttress the main determinants.